Effect of CNT and TiC hybrid reinforcement on the micro-mechano-tribo behaviour of aluminium matrix composites. (2020) - Nayim, S.M. Towhidul Islam; Hasan, Muhammed Zahid; Seth, Prem Prakash; Gupta, Pallav; Thakur, Sunil; Kumar, Devendra; Jamwal, Anbesh
Abstract: In the present study Aluminium-3003 alloy metal matrix reinforced with single walled CNTs and TiC were fabricated with stir casting process. Aluminium matrix composites found many applications in aerospace and structural engineering. In this study wt.% of CNT is fixed as 0.5 wt.% and TiC content is varied from (0.5 wt.%–2 wt.%) at an interval of 0.5 wt.% Microstructural, Mechanical and Tribological behaviour of composites were investigated. It is found that with increase in reinforcement content uniform dispersion of particles is found. Density of composites is decreased due to volatile nature of reinforcement particles. Hardness of composites is increased with increase in reinforcement content. Wear rate of composites is lower at lower loads and also at higher reinforcement contents.